Settlement of Abuse of Authority Relating to the Independence of the Curator Based on Law Number 37 of 2004 Concerning Bankruptcy and Suspension of Debt Payment Obligations - Yulia Putri Maulina; Teuku Syahrul Ansari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The curator has the principle of independence and impartiality which is one of the main principles recognized and desired by Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The curator is responsible for errors or negligence in carrying out the duties of managing and settling the bankruptcy estate. Bankruptcy occurs due to bankruptcy experienced by a company. Bankruptcy is part of civil law. However, several bankruptcy cases eventually developed into crimes when the bankruptcy curator who was tasked with handling and administering bankruptcy cases abused his authority, especially in relation to independence. The complexity of resolving bankruptcy assets is further increased by the inclusion of a criminal sanctions article in the Bankruptcy Law which states that if it is proven that the curator is not independent, he can be subject to legal sanctions, both criminal and civil, in accordance with the law.